Acute inflammation down‐regulates alpha‐synuclein expression in enteric neurons. Issue 6 (24th January 2019) - Prigent, Alice; Gonzales, Jacques; Durand, Tony; Le Berre‐Scoul, Catherine; Rolli‐Derkinderen, Malvyne; Neunlist, Michel; Derkinderen, Pascal
Abstract: The protein alpha‐synuclein whose expression is strongly implicated in Parkinson's disease (PD) is not only expressed in the CNS but also in the enteric nervous system (ENS). The growing body of evidence suggesting that gastrointestinal inflammation is involved in the development of PD led us to investigate the effects of inflammation on alpha‐synuclein expression in primary culture of rat ENS and in mice with dextran sulfate sodium‐induced colitis. Using western blot and qPCR, we found that both lipopolysaccharide and a combination of tumor necrosis factor‐α and interleukin 1‐β decreased the expression levels of alpha‐synuclein in primary culture of rat ENS, an effect that was prevented in the presence of the p38 inhibitors SB203580 and BIRB 796. Lipopolysaccharide and tumor necrosis factor‐α/interleukin 1‐β had no effect on alpha‐synuclein expression in primary culture of rat CNS and in human erythroid leukemia cells. In mice, acute but not chronic dextran sulfate sodium‐induced colitis was associated with a decreased expression of colonic alpha‐synuclein. As a whole, our findings indicate that acute inflammatory insults down‐regulate alpha‐synuclein expression in the ENS via a p38 pathway. They provide new insights into the widely discussed concepts of alpha‐synuclein expression and aggregation in the ENS in PD and raise issues about the possible role of gastrointestinal inflammation in the development of PD. Open science badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : We show that acute inflammatory insults down‐regulate alpha‐synuclein expression in primary culture of enteric nervous system and in the colon of mice. Our findings provide new insights into the widely discussed concepts of alpha‐synuclein expression and aggregation in the enteric nervous system in Parkinson's disease and raise issues about the possible role of gastrointestinal inflammation in the development of Parkinson's disease. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/